Prospects for the development of digital financial services in commercial banks of Uzbekistan - Murtazaev Nurbek Rashidovich (THE INNOVATION ECONOMY, 2026)
Scientifically based theoretical and methodological methods for creating digitized banking products in commercial banks, formulating odern banking product offers to bank customers, ensuring full satisfaction of their needs for products and services, ensuring the bank's competitiveness in the financial market, increasing profitability and profitability consists of developing rules and practical recommendations.